(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Slightly edited keynote presented at the International Conference Towards Humanising the Future. Justice in the Shadow of Colonialism. A Transformative Learning Approach at the Pädagogische Hochschule Freiburg, 29 September 2022.